2019
DOI: 10.1007/s11419-019-00504-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the administration of ecdysterone in doping control samples

Abstract: The phytosteroid ecdysterone was recently reported to enhance performance in sports and may thus be considered as a substance of relevance in anti-doping control. To trace back an administration of ecdysterone from urine samples analytical properties have been investigated to assess its integration into initial testing procedures (ITP) in doping control laboratories. MethodsAnalytical properties of ecdysterone were evaluated using GC-QTOF-MS and LC-QTOF-MS.Its metabolism and elimination in human were studied u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 30 publications
(43 reference statements)
2
33
0
1
Order By: Relevance
“…Such experiments paved the way, directly or indirectly, for use as a "doping substance" by sportsmen or bodybuilders based on the consumption of uncontrolled dietary supplements [162]. The recent confirmation of these anabolic results [163] led the authors to propose the inscription of 20E on the list of doping prohibited substances [164].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Such experiments paved the way, directly or indirectly, for use as a "doping substance" by sportsmen or bodybuilders based on the consumption of uncontrolled dietary supplements [162]. The recent confirmation of these anabolic results [163] led the authors to propose the inscription of 20E on the list of doping prohibited substances [164].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Studies on the metabolism of ecdysterone have been conducted mostly in animals and only a few refer to humans [10,[30][31][32][33][34]. While ecdysterone does not seem to undergo phase II metabolism [30,34], studies concur on its biotransformation, leading to the formation of dehydroxylated metabolites. However, structure assignment and information on the excretion profiles differ in some studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in a single dose administration study, 51.5 mg of pure ecdysterone has been administered to one healthy volunteer, and the presence of 14-deoxy-ecdysterone was confirmed in the post-administration urine samples, in comparison to the in-house synthesized reference [34]. Parr et al reported ecdysterone as the most abundant analyte in post-administration urine samples, with a wider detection window than 14-deoxyecdysterone, which was excreted later [34].…”
Section: Introductionmentioning
confidence: 99%
“…More studies are needed to clarify the exact mode of action. Maral root extract and 20-hydroxyecdysone are currently legal; however, 20-hydroxyecdysone was recently included in the WADA monitoring list [102]. Ashwagandha or Indian ginseng (Withania somnifera; Solanaceae) has recently received attention as a supplement that can increase muscle mass, strength, and overall fitness.…”
Section: Testosterone Boostersmentioning
confidence: 99%